2020
DOI: 10.1159/000506898
|View full text |Cite
|
Sign up to set email alerts
|

TNF-Alpha Blockers in Inflammatory Bowel Diseases: Practical Recommendations and a User’s Guide: An Update

Abstract: a on behalf of the Swiss IBDnet, an official working group of the Swiss Society of Gastroenterology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 87 publications
(105 reference statements)
2
45
2
Order By: Relevance
“… 24 , 30 Considering the lack of standardized strategies for ATI management, IFX therapies are sometimes merely IFX trough level guided. 1 , 10 14 Notably, IFX levels and related indices did not predict LOR in our study. Regarding the S ATI group comparisons, this surprising observation may, on the one side, be caused by limiting the analyzed data to the time window T 0–3 .…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“… 24 , 30 Considering the lack of standardized strategies for ATI management, IFX therapies are sometimes merely IFX trough level guided. 1 , 10 14 Notably, IFX levels and related indices did not predict LOR in our study. Regarding the S ATI group comparisons, this surprising observation may, on the one side, be caused by limiting the analyzed data to the time window T 0–3 .…”
Section: Discussioncontrasting
confidence: 74%
“…TNF antagonists are considered as disease-modifying drugs and constitute powerful tools to achieve clinical and endoscopic remission. 1 After initial approval, TNF antagonists were indicated as penultimate measure before surgery within the step-care approach. Nowadays, the use of TNF antagonists has shifted toward early intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Several trials have demonstrated the efficacy of infliximab in induction and maintenance of remission of CD and UC in patients and subsequently further trials showed adalimumab has a similar therapeutic benefit in inducing and maintaining remission of disease leading to their use for UC and CD in clinical practice. Golimumab has since been shown to have efficacy in UC and certolizumab in CD; the latter is approved for CD in US but not in EU [65] , [66] .…”
Section: Role Of Tnf-alpha Inhibitors In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Interestingly, DSSregulated genes of Th17 cells in cluster 0 were highly enriched in TNF and NFB signaling pathways. TNF antagonists have been the mainstay in the treatment of inflammatory bowel diseases (IBD) for over 20 years (Vulliemoz et al, 2020), and the NFB pathway is known to be activated in inflamed colonic tissue from IBD patients (Atreya et al, 2008;Liu et al, 2017). It would be interesting for future studies to explore whether Th17 cells subset in cluster 0 is targeted by anti-TNF therapies in human IBD.…”
Section: Discussionmentioning
confidence: 99%